Advancing Secure Communication in the Quantum Era through the Integration of Artificial Intelligence and Quantum Cryptographic Techniques: Author's Country: India - Hemant N Chaudhari; Bayu Priyatna; Agustia Hananto (Information System; Universitas Buana Perjuangan Karawang, 2026)
Utilizing the ideas of quantum physics, quantum cryptography is quickly becoming a vital defense against the growing cybersecurity risks of the contemporary day, especially in light of developing quantum computing. This essay investigates the complex field of quantum cryptography and looks at how it can transform network security and protect private data. We examine the fundamental ideas of quantum cryptography, such as Quantum Key Distribution (QKD) protocols like BB84 and E91, which use quantum features like superposition and entanglement to provide potentially indestructible secure communication channels. We also discuss the urgent need for quantum-resistant solutions in view of the developing